PENGARUH PENAMBAHAN EKSTRAK JAHE MERAH (ZINGIBER OFFICINALE ROSCOE) TERHADAP KARAKTERISTIK BAKSO IKAN PATIN (Pangasius, sp) - Aisyah, Siti; Adawyah, Rabiatul; Puspitasari, Findya; Rohman, Taufiqur (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2025)
This study aims to investigate the effect of adding red ginger extract (Zingiber officinale Roscoe) on the chemical characteristics (moisture content and protein level) and organoleptic properties (color, aroma, taste, and texture) of catfish (Pangasius sp.) meatballs. The study used a Completely Randomized Design (CRD) with six treatment concentrations of red ginger extract: 0%, 12%, and 18%, each with three replications. The results showed an increase in moisture content from 55.10% to 61.19% and protein content from 10.50% to 12.99% as the concentration of red ginger increased. Organoleptic testing indicated the highest hedonic scores were observed at the 6% treatment level across all sensory parameters.